The use of an action learning strategy in teaching speaking at the eleventh-grade students of MTS MIM Langsa - Ramadhani, Mashitah; Wati, Shafrida; Wahidah, Wahidah (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2022)
This study describes the implementation of action learning strategy in teaching speaking to eighth-grade students of MTs. MIM Langsa. It applies Classroom Action Research (CAR). The research subject was 30 students of eleventh graders in the academic year of 2020/2021. This research was conducted in two cycles consisting of planning, acting, observing, and reflecting. Data were collected through observation and tests. The finding shows that the application of action learning strategies helps the students to improve their speaking skills. This was identified by the result of the mean score of the second cycle was 73.16. This showed that the score was improved than the first cycle. The percentage of students who obtained >71 points also increased. Test of the cycle I indicated that only about 8 students obtained scores>71 (26.66%). While in cycle II, those who obtained scores>71 was 72% or about 24 students. This indicated that the score reached the KKM and it was concluded that the students’ speaking ability was increasing. They were also more active and participative in the teaching and learning process.